The Maslach-Trisni Burnout Inventory: Adaptation for Indonesia - Lucia Trisni Widhianingtanti; Gilles van Luijtelaar (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2022)
Burnout is commonly measured with the Maslach Burnout Inventory (MBI), which consists of three subscales measuring emotional exhaustion, personal accomplishment, and cynicism. We adapted the scale and then explored and confirmed the three dimensions on the Indonesian version named The Maslach-Trisni Burnout Inventory (M-TBI) with an exploratory analysis followed by Confirmatory Factor Analysis (CFA) from 822 workforces. The sensitivity for different job characteristics and demographic factors was established with analyses of variance and based on percentile scores of the subscales, three categories for burnout tendency were proposed. The scores on the three subscales were compared with those of Western countries. There are similar scores for emotional exhaustion and cynicism, but the sample score for personal accomplishment tends to be lower than the western countries. It can be concluded that the M-TBI scale is a reliable, sensitive, and efficient tool to measure the burnout tendency in the workforce in Indonesia.